Legal Responsibility For Corporations Regarding The Crime Of Illegal Fishing In Indonesia - T. Riza Zarzani; Ismaidar Ismaidar; Welli Nirpa Pasaribu (International Journal of Law and Society, 2024)
Indonesia is known as the largest archipelagic country in the world and is recognized as having a maritime territorial area that is almost equal to its land area. Indonesia's territorial waters contain abundant potential fishery resources and marine diversity, making it known as a maritime country. Illegal fishing is an activity or fishing activity that is contrary to a country's laws or international regulations, where the majority of perpetrators are corporations. Illegal fishing practices have a tremendous impact on marine sustainability, causing huge losses to the country. The occurrence of illegal fishing is caused by weak law enforcement and supervision in Indonesian waters and the authorities' indecisiveness in handling illegal fishing perpetrators. Understanding illegal fishing and crimes committed by corporations should be a strong basis for every legal practitioner to process and impose appropriate and correct sanctions on every perpetrator of illegal fishing or corporate crime perpetrators. The method used in this research is a normative legal research method sourced from primary data, namely the Criminal Code (KUHP), Law Number 45 of 2009 in conjunction with Law Number 31 of 2004 concerning Fisheries, Law of the Republic of Indonesia Number 32 of 2009 concerning Environmental Protection and Management (UUPPLH), secondary data and tertiary data based on regulations relating to fisheries and corporate crimes. The data collection method is qualitative descriptive analysis with literature study using a statute approach. This research aims to determine the factors that cause the crime of illegal fishing in Indonesia, the legal responsibility of corporations related to the crime of illegal fishing in Indonesia and the efforts made to prevent or eradicate the occurrence of criminal acts. illegal fishing in Indonesia.